Factors associated with cognitive and motor development among infants aged 6 to 12 months in Seremban, Negeri Sembilan, Malaysia - Sabri, Nur 'Amirah 'Inani (2019)
The development of cognitive and motor skills early in life is essential for a child’s global development and learning, which in turn influences later health and well-being. Developmental delay of infants is an important public health issue that warrants further investigation as infants with developmental delay require more attention and healthcare services than the general population. However, little research has examined cognitive and motor development of infants. Thus, this cross-sectional study aimed to determine the factors associated with cognitive and motor development among infants aged 6 to 12 months. A total of 200 mother-infant pairs were recruited from three randomly selected maternal and child health clinics in Seremban, Negeri Sembilan. A face-to-face interview was conducted with the mothers in the health clinics to collect information on sociodemographic background and infant feeding practices by using Infant and Child Feeding Index (ICFI) and 24-hour dietary recall. Body weight and length of the infants were measured to determine their growth status. Furthermore, a heel prick test on hemoglobin status was conducted by a nurse in the health clinic on the infants with parental consent. Cognitive and motor development of the infants was assessed using the Bayley Scales of Infant Development, Third Edition (Bayley-III) by the researcher. Birth record of the infants were obtained from their health record book. Results showed that 37.0% of the infants in this study were found to have cognitive developmental delay, while 58.0% had motor developmental delay. The prevalence rates of underweight, stunting, wasting, possible risk of overweight, and overweight were 6.5%, 9.5%, 15.0%, 6.5%, and 3.5%, respectively. About two in five of the infants (42.4%) were anemic. In term of feeding practices, 50.5% of the infants were not exclusively breastfed for the first 6 months of life and 12.0% started complementary feeding at age less than 6 months. Moreover, according to the ICFI classifications, 64.1% of the infants aged 6 to 8 months and 63.6% of the infants aged 9 to 12 months reported to have a low child feeding index. About one in three of the 6 to 8 months infants (30.8%) and 25.0% of the 9 to 12 months infants did not achieve the recommended intake for energy. Some 37.8% and 18.2% of the infants aged 6 to 8 months and 9 to 12 months, respectively, did not achieve the recommended intake for protein. Multiple logistic regression results showed that infants with gestational age less than 37 weeks (AOR=5.99, 95% CI=1.96-18.33, p=0.002), anemic (AOR=3.47, 95% CI=1.18-10.22, p=0.024), and from single/divorced mothers (AOR=15.80, 95% CI=2.64-94.58, p=0.003) were found to be significantly associated with increased risk of cognitive developmental delay, in which they explained 42.3% of the variance in cognitive developmental delay among infants aged 6 to 12 months in this study. On the other hand, boys (AOR=7.38, 95% CI=2.76-19.74, p<0.001), anemic infants (AOR=2.65, 95% CI=1.22-5.73, p=0.014), and non-exclusively breastfed infants (AOR=2.76, 95% CI=1.17-6.49, p=0.020) were found to be significantly associated with increased risk of motor developmental delay, in which they explained 28.9% of the variance in motor developmental delay in this study. Anemia status was consistently predicted both cognitive and motor developmental delays in infants aged 6 to 12 months in this study. In conclusion, high prevalence of cognitive and motor developmental delays among infants aged 6 to 12 months in this study highlights the need for early identification and interventions in order to improve early childhood development. An advocacy effort is needed for implementing early intervention programs involving parents, communities and government agencies to improve cognitive and motor development of infants. Nutrition education programs and interventions for mothers should emphasize exclusive breastfeeding practices and the prevention of anemia in infants in order to improve cognitive and motor development of infants.